The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2002
DOI: 10.1075/lplp.26.1.02mul
|View full text |Cite
|
Sign up to set email alerts
|

Addressing counterterrorism

Abstract: The terrorist attacks of 11 September 2001 in New York and Washington, DC, have caused a significant review of US capacity to conduct intelligence analysis to predict such attacks. A key component of the ability to analyze intelligence is the matter of competence in languages appropriate to areas of current emphasis in national defense. Language capacity is not a new topic to national defense, but this article looks at the link between government needs for language capacity and the availability of languages in… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
5
0

Year Published

2003
2003
2009
2009

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(5 citation statements)
references
References 0 publications
0
5
0
Order By: Relevance
“…Curiously, this issue seems to have been much more of a conundrum in Englishspeaking countries, where jubilation about the expansion of English -'Christmas special: the triumph of English' (Economist, 22 December 2001: 65) -comes concurrently with warnings about the limits of English, and how English-speaking countries need to attend to other languages for a variety of economic or security reasons (Berlinski, 2001;Müller, 2002). In non-English-speaking countries there 70 Current Issues in Language Planning…”
Section: Language As a Resource: Trade And Foreign Language Learningmentioning
confidence: 98%
“…Curiously, this issue seems to have been much more of a conundrum in Englishspeaking countries, where jubilation about the expansion of English -'Christmas special: the triumph of English' (Economist, 22 December 2001: 65) -comes concurrently with warnings about the limits of English, and how English-speaking countries need to attend to other languages for a variety of economic or security reasons (Berlinski, 2001;Müller, 2002). In non-English-speaking countries there 70 Current Issues in Language Planning…”
Section: Language As a Resource: Trade And Foreign Language Learningmentioning
confidence: 98%
“…Increased attention to the role of formal instruction in maintaining heritage languages has come about as a consequence of the events of September llth, which brought to the nation's attention the strategic importance of "foreign" languages. As a result, the intelligence and military communities (Muller, 2002) have expressed a growing interest in expanding the nation's linguistic resources by both teaching non-English languages and by maintaining the heritage or home languages of the 47 million individuals who reported speaking both English and a non-English language in the latest census in 2000 (U.S. Census Bureau, 2003). For many individuals concerned about language resources, the development of strategic languages can only be brought about by expanding the mission of foreign language departments to include the maintenance and expansion of the varieties of non-English languages currently spoken by immigrants, refuigees, and their children.…”
Section: Language Instruction and Heritage Speakers In The United Statesmentioning
confidence: 99%
“…By the 1990s, concern about the deficit in language capability had spread to the U.S. House of Representatives Select Committee on Intelligence, which reported that America lacked even a rudimentary capability in Middle Eastern languages (Muller 2002:3). As Figure 4 reveals, a study done of university‐level language study in 1998 revealed that only about 5,000 students (most of them Arab Americans) were taking courses in Arabic (Brod and Welles 2000).…”
Section: Linguistic Xenophobiamentioning
confidence: 99%
“…By 2002, the U.S. federal government was actually losing more Arabic speakers than it was able to hire (GAO 2002). The same year, the House Select Committee on Intelligence complained that the “CIA, NSA, FBI, DIA and the military services ... have all admitted they do not have the language talents, in breadth or in depth, to fully and effectively accomplish their missions” (Muller 2002:4). Journalist Bob Woodward (2006:204) reported that when the U.S. government provided to Saudi officials the English‐language, translated versions of National Security Agency–intercepted al‐Qaeda communications, the Saudis complained that the English versions were incomprehensible and demanded to see the Arabic originals.…”
Section: Linguistic Xenophobiamentioning
confidence: 99%
See 1 more Smart Citation